Desempenho muscular de indivíduos na fase inicial da doença de Parkinson - Lidiane Andrea Oliveira Lima (2008)
Parkinsons Disease (PD) is a chronic neurodegenerative disease with an important impact in the life of the patient and society. Its common motor symptoms are: resting tremor, bradykinesia, rigidity and postural instability which occur in later stages of the disease. The progression of the symptoms determines the motor incapacity of the individual with PD and its also associated with peripheral deficits such as progressive loss of muscular mass, weakening of the muscular strength and resistance, the diminishment of the physical abilities. Changes in the muscle strength in advanced phase of PD are a common find and the disability for the individual. However, even in the early phase, individuals with PD can present a loss of muscular strength. The literature has shown deficits in the torque and muscular strength in different stages of PD with differences between members more and less affected by Parkinsons syntomatology. However, the results are controversial in relation to the asymmetry in the early phase of the disease. It has been suggested that individuals with PD presents a deficit in the activation of the extensor muscles what would contribute to the posture clinically observed in the advanced stages of PD. Some studies have suggested that this deficit could be present since the early phase of the disease. The objective of this present study was to compare the measurement of muscular performance of flexor and extensors in the trunk, hips, knee and ankle between individuals in the early phase of PD and individuals without the disease; to compare measurement of muscular performance of flexors and extensors of the hips, knee and ankle and in the inferior members more and less affected in individuals in the early phase of PD; and to compare the measurement of muscular performance between flexors and extensor of the trunk, hips, knee and ankle of the individual in the early phase of PD. Twenty individuals above 50 years old participated in this study; they were divided in two groups: one experimental group made up of 10 individuals with PD in the in early phase and the control one made up of 10 individuals without PD, age, level of physical activity, sex, height and weight matched. The isokinetic dynamometer Biodex System 3 Pros® (Biodex Medical Systems Inc., Shirley, NY, USA) was used for the evaluation of the muscular performance of the flexors and extensors of the hips, knees, ankles and trunk of the individuals with or without PD. The variables evaluated in this study were total work and medium power normalized by the body weight in agonist/antagonist relation in the angular speed of 30 º/s (slow) and 90º/s (fast), in a concentric-concentric for the inferior members and 120º/s for the trunk. The data analysis was made with a program SPSS (version 15.0 for Windows) and the analysis of variance (ANOVA) mixed for the repetitive measurements for two factorials levels. The individuals in the early stage of PD the present study exhibited a muscular performance notably inferior in the legs and trunk when compared with the individuals without the disease. The group with PD presented worse muscular performance especially in the axial and proximal muscles of the body in relation to the distal muscles. It was also observed a worse performance in the non-dominant inferior member in the control group and the member more affected in the group with PD, especially in the higher speed. The variable reason agonist/antagonist didnt exhibit a meaningful difference in the groups and inferior members and neither one of the muscle groups tested. The individuals in the early phase of the present study displayed worse muscular performance in the inferior members and the trunk, when compared with the individuals without the disease. The results also indicated that the flexor muscles and extensors of the axial and proximal areas of the body can be affected earlier by PD in relation to the distal muscles. In addition, the groups presented an asymmetrical muscular performance between the inferior members.